les ondelettes et leurs applications aux intéqrations numériques - azizi, atika; charrahi, sara (جامعة الوادي University of Eloued, 2019)
"ملخص هذه المذكرة، مخصصة لدراسة التأثیر التطبيقي لطرق العددية لحل التكامل العددي. نبدأ بتذكیر حول الدوال الحقيقية أین سنقدم نظريات ومفاهيم أساسية مثل: التزيدات المنتهية، نشر تایلور، كثیر الحدود المستقطب. من بعد النظريات التقلیدية للتكامل العددي ك: )شبه المنحرف، ترابیز وسيمسون(. وأخیر نختم بنظرية المويجات لهار مع أمثلة م"This work is devoted to the study of practical effect of numerical methods to solve numerical integration. We start with a reminder about the real functions, where we quote some main theorems and notions for example the theorem of finite increments, the Taylor formulas and limited developments and the interpolation polynomial. Then the classical methods of numerical integration for example (rectangle, Trapeze and Simpson). Finally we conclude with Haar wavelet theory with illustrative examples that show the efficiency of this method from a comparison of the absolute error results of each method."بینة تقدم مدى فعالية هذه الطريقة من خلال المقارنة بین نتائج القيم للخطأ المطلق."
mémoire master mathimatique
Keywords: الكلمات المفتاحة: التكامل العددي الطريق التربيعة، مويجات، تحلیل متعدد الحلول.; Keywords: numerical integration, quadrature method, wavelets, multiresolution analysis.